Determinants of Lung Function Disorders in Rice Milling Workers in Kabila District, Bone Bolango Regency - Sitty Afifah Pone; Herlina Jusuf; Tri Septian Maksum (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Impaired lung function in workers is influenced by factors of the working environment and individual characteristics. At the rice mill in Kabila District, Bone Bolango Regency, problems were found in the form of high levels of rice dust of the PM₁₀ fraction. This study aims to analyze the determinants of lung function disorders in rice milling workers in Kabila District, Bone Bolango Regency. Analytical observational research methods with cross-sectional design. The research population of all workers in five rice milling units, namely Mustika, Mutiara, Oluhuta, Helumo, and HP. Using a total sampling technique of 33 workers. Data was collected using interview guidelines, observation sheets, Peak Flow Meter to measure lung function, PM 10 fraction dust measuring device. Data analysis was carried out using the Fisher Exact test. The results showed that there was no association between the level of rice dust of the PM₁₀ fraction (p=0.136) and working period (p=0.359) with impaired lung function, while length of work (p=0.036) had a significant relationship with impaired lung function in rice milling workers. The conclusions showed that length of work was associated with impaired lung function in rice milling workers, while the level of PM₁₀ fraction rice dust and the working period were not associated with impaired lung function. It is recommended that workers limit working hours and use PPE consistently, and rice mill owners need to regulate working hours and provide a healthy working environment.